2009
DOI: 10.1021/jp906764e
|View full text |Cite
|
Sign up to set email alerts
|

Cation Disorder in Pyrochlore Ceramics: 89Y MAS NMR and First-Principles Calculations

Abstract: The use of first-principles DFT calculations to interpret solid-state 89Y MAS NMR spectra of Y2Ti2-x Sn x O7 pyrochlores, materials with applications for the encapsulation of actinide-bearing radioactive waste, is investigated. Although NMR is a sensitive probe of local structure, which does not rely on the presence of long-range order, spectra of disordered materials are often complex and difficult to interpret. We show how calculations can be used alongside experiment to confirm that Y occupies only the eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
133
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(154 citation statements)
references
References 28 publications
21
133
0
Order By: Relevance
“…[31] Recent papers proved that 89 Y NMR spectroscopy is a useful probe for local ordering in solid-state compounds. [38][39][40][41] Consequently, we performed 13 (Figures 2 and 3) show no evidence of local ordering and support the interpretation of randomly distributed yttrium and lanthanum atoms. Figure 2 clearly shows that regardless of the lanthanum doping rate, the 89 Y NMR signal remains almost identical.…”
Section: Resultssupporting
confidence: 69%
“…[31] Recent papers proved that 89 Y NMR spectroscopy is a useful probe for local ordering in solid-state compounds. [38][39][40][41] Consequently, we performed 13 (Figures 2 and 3) show no evidence of local ordering and support the interpretation of randomly distributed yttrium and lanthanum atoms. Figure 2 clearly shows that regardless of the lanthanum doping rate, the 89 Y NMR signal remains almost identical.…”
Section: Resultssupporting
confidence: 69%
“…This work was recently extended to use first principles DFT calculations. The shift values calculated and the effects of the Ti,Sn ordering confirmed that the yttrium does remain eight-fold coordinated and that B site occupancy is random [53]. 109 Ag NMR is another low-nucleus and an extensive study of 20 simple inorganic silver salts added a large amount of new 109 Ag data to the literature [54].…”
Section: Progress In Observation Of Less Studied Nucleimentioning
confidence: 75%
“…When considering B-site substitution, it is impractical to perform calculations on truly disordered solids (as an unfeasibly large number of atoms would be involved), and a simplified approach is required. 16 The pyrochlores. 19 The combination of high-resolution NMR and GIPAW DFT calculations enables detailed information to be obtained about the nature of the B-site cation disorder in pyrochlores and provides detailed insight into the local geometry -information it is difficult to obtain from diffraction-based methods.…”
Section: Cation Disorder In Pyrochlore Ceramicsmentioning
confidence: 99%